2023
DOI: 10.3390/ani13142308
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anti-Coccidial Compounds and Phytogenic Saponin Extracts on In Vitro and In Vivo Ruminal Fermentation and Methane Production of Cattle

Abstract: Four experiments were conducted to evaluate sources of anti-coccidial compounds and phytogenic saponin extracts on in vitro and in vivo ruminal fermentation and CH4 production at multiple inclusion levels. In experiment 1, eight steers were fed either a finishing diet or a finishing diet supplemented with 0.5 mg/kg BW decoquinate (DCQ) and 3.33 mg/kg BW Yucca schidigera extract (YSE), and respiratory gas exchange was measured. In experiment 2, four ruminally-cannulated steers were fed the same treatments as ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…The current study showed that YSE had a positive effect on the ADG, and this finding was similar to those in previous reports [ 5 , 9 , 10 ]. A higher DMI as a result of YSE supplementation was found by Abdel-Raheem [ 14 ], and the same finding was observed in this experiment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study showed that YSE had a positive effect on the ADG, and this finding was similar to those in previous reports [ 5 , 9 , 10 ]. A higher DMI as a result of YSE supplementation was found by Abdel-Raheem [ 14 ], and the same finding was observed in this experiment.…”
Section: Discussionsupporting
confidence: 93%
“…Saponin is a natural cholesterol binder that can produce a stable linkage to cholesterol on the surface of the cell membrane of a protozoan so that the integrity of the cell membrane is broken, resulting in cell lysis [ 8 ]. The energy utilization in beef cattle was increased as the YSE decreased the number of protozoa, resulting in lower methane production [ 9 , 10 ]. Commercially, YSE, as a feed additive, is also used to control ammonia emissions and environmental impact from livestock and poultry facilities to reduce odor impact [ 11 ].…”
Section: Introductionmentioning
confidence: 99%